The effectiveness of targeted wage subsidies for hard-to-place workers - Ursula Jaenichen; Gesine Stephan (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
Targeted wage subsidies paid to employers are an important element of active labour market policies in Germany. This paper uses propensity score matching to investigate their effect on subsidised hard-to-place workers. In a first scenario, we estimate the average treatment effect of a subsidy on previously unemployed individuals. A second scenario analyses the effects of a subsidy on employment probabilities conditional on takingup employment. The third scenario investigates the additional effect of a subsidy on individuals, who have participated in a short-term training measure beforehand. Summing up and in line with the literature, the results show that subsidies have a favourable effect on the employment prospects of participants.
Keywords: J68; J64; J65; 330; Targeted wage subsidies; evaluation of labour market programmes; propensity score matching